Implementasi Metode Show And Tell Terhadap Keterampilan Berbicara Siswa Kelas V SD Negeri 14 Palu - Rizal; Zulnuraini; Sri Lestari; Muhammad Aqil; Muhammad Fasli (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2025)
Speaking skills are an important aspect in the academic and social development of elementary school students. However, fifth grade students of SD Negeri 14 Palu still have difficulty in communicating actively during learning, characterized by a passive attitude and lack of courage to speak. This study aims to determine the implementation of the show and tell method in learning Indonesian in fifth grade of SD Negeri 14 Palu. This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the show and tell method is implemented through five main stages, namely: (1) introduction of the method to students, (2) modeling by the teacher as an example, (3) implementation of show and tell activities by students by showing and explaining an object, (4) observation and providing feedback by the teacher, and (5) question and answer session. The obstacles faced include student readiness, differences in speaking skills, and time constraints. However, the teacher tries to overcome them through additional guidance and motivation. The application of this method provides benefits for students, especially in speaking skills, namely choosing appropriate words, better language skills, courage to speak in front of the class, fluency in speaking, and better mastery of the material. Thus, the results of this study indicate that the show and tell method can be implemented effectively in learning to support better speaking skills in elementary school students.